GAMBARAN KESEHATAN MATA PADA ANAK USIA SEKOLAH - Dinul Tauhid Almaturidi; Riri Novayelinda; Herlina Herlina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2022)
School age is a period of physical characteristic of the eye get mature. Earlier eye examination is very important to detect any vision impairment. The purpose of this study is to know the eye healthiness of the children in school age. This is a descriptive research with cross sectional approach. The sample of this study is 50 respondents, based on inclusive criteria in the area of Pekanbaru City using accidental sampling technique. This study is measured using Portable Eye Examination Kit (PEEK) Acuity to measure the vision acuity. The analysis of the study was presented with a table frequency distribution with cross tabulation. Obtained 26 respondents (52%) with impaired vision acuity, the highest is in the 8-10 years age category of 16 people (55.2%) and in the female category there were 10 people (58.8%). School age children who experience more visual impairment. Researcher suggest to do more frequent and thorough screening to children in school age, specifically in Pekanbaru. Keywords: Vision, PEEK Acuity, school age